Daratumumab resistance is frequent in advanced‐stage multiple myeloma patients irrespective of CD38 expression and is related to dismal prognosis. (25th March 2018) - Pick, Marjorie; Vainstein, Vladimir; Goldschmidt, Neta; Lavie, David; Libster, Diana; Gural, Alexander; Grisariu, Sigal; Avni, Batia; Ben Yehuda, Dina; Gatt, Moshe E.
Abstract: Objective: Daratumumab is a promising new antimyeloma agent. We report a single center "real‐world" series of multiple myeloma (MM) and amyloidosis (AL) patients treated with daratumumab. Methods: Forty‐one patients were included: 7 second‐line MM, 30 heavily pretreated (median number of therapies of 5) advanced MM, and 4 with AL. Results: Second‐line patients and advanced AL showed high rate of durable overall responses. However, advanced MM patients had a dismal prognosis with an overall response rate (ORR) of 36%, and a short median progression‐free and overall survival of 2.3 and 6.6 months, respectively. Responses were particularly poor in patients with extramedullary plasmacytomas. Neither the addition of another agent to daratumumab nor changing to the next line of therapy produced significant durable responses in this patient population. Flow cytometry analysis demonstrated that CD38 expression level was not predictive of response. We show that CD38 expression dynamics by a commercially available anti‐CD38 antibody after daratumumab administration was hindered by competitive binding of daratumumab. Conclusions: Responses to daratumumab and combinations in patients with advanced MM, particularly with extramedullary disease, are low and short‐lived, stressing the administration of this agent should be early in the course of the disease.